Prolonged overall survival in a child with multimetastatic retinoblastoma treated with anti-GD2 monoclonal antibody dinutuximab beta: a case report - Di Ruscio, Valentina; Carboni, Alessia; Del Baldo, Giada; De Pasquale, Maria Debora; Valente, Paola; Di Giannatale, Angela; Serra, Annalisa; De Vito, Rita; Mastronuzzi, Angela; Quintarelli, Concetta; De Angelis, Biagio; Milano, Giuseppe Maria; et al. (Frontiers in Oncology, 2025)
High-dose chemotherapy with autologous stem cell rescue has improved outcomes in patients with metastatic retinoblastoma (RB). However, significant short- and long-term toxicities—especially in very young children with a constitutional RB1 gene mutation—highlight the need for alternative therapeutic strategies. Monoclonal antibodies targeting tumor-associated antigens such as GD2 have emerged as promising agents in this setting. We report the case of a 2-year-old child diagnosed with extensive left-eye retinoblastoma and massive extraocular dissemination at presentation. The patient was treated with systemic conventional and high-dose chemotherapy combined with intrathecal Topotecan. As consolidation therapy, the child received three courses of the anti-GD2 monoclonal antibody Dinutuximab beta over a 10-day schedule. The patient achieved complete remission and remains disease-free six years after the initial diagnosis. This case suggests that anti-GD2 immunotherapy, used as consolidation treatment, may improve the prognosis of patients with advanced retinoblastoma and potentially reduce the toxicity associated with standard therapies. Further clinical investigation is warranted to validate these findings.